Fuzzy voting algorithms for N-version software - Tsarev, R. Y.; Durmus, M. S.; Ustoglu, I.; Morozov, V. A.; Pupkov, A. N. (IOP PUBLISHING LTD, 2019)
The choice of the voting algorithm in N-version programming directly affects the evaluation of the results of N software versions and determines the correct result. The result of the voting algorithm is also the outcome of the N-version software. Therefore, the choice of the voting algorithm is vital. However, many voting algorithms were already developed and they may be selected for implementation, based on the specifics of the analysis of input data of these algorithms. This article presents a brief overview of major fuzzy voting algorithms.
Keywords: BEHAVIOR; SYSTEMS; Automation & Control Systems; Engineering; Mathematics